Psychiatric Comorbidity in Patients of OCD: How Severe is Anxiety and Depression? - Kaur, Dr. Navdeep; Garg, Dr. P. D; Arora, Dr. Rajiv (International Journal of Innovative Research in Medical Science, 2018)
Introduction - OCD is a debilitating illness characterized by obsessions and compulsions. It affects 1-3% of population. Many psychiatric illnesses are common with it. Anxiety and depression are commonest disorders. AIM - To study severity of OCD, to study severity of anxiety and depression and other psychiatric comorbidity. Method - A cross-sectional study of 45 patients conducted in department of Psychiatry, GMC, Amritsar. Diagnosis was confirmed using ICD-10criteria.M.I.N.I, HAM-A,HAM-D,Y-BOCS were used to assess comorbidity , severity of OCD, depression and anxiety. Results - Majority of patients suffering from OCD had a chronic course with adolescent onset with male predominance and most of them had comorbid psychiatric disorder, commonest being MDD, anxiety disorders, substance abuse, BPAD etc .Relationship of YBOCS with HAM-D came out to be highly significant p-value <0.001,relationship of YBOCS with HAM-A was not significant p-value=0.202.